A Review on Molecular Mechanisms and Patents of Marine-derived Anti-thrombotic Agents - Doshi, Gaurav; Nailwal, Namrata (Current Drug Targets, 2021)
Thrombosis is a condition of major concern worldwide as it is associated with life-threatening diseases related to the cardiovascular system. The condition affects 1 in 1000 adults annually, whereas 1 in 4 dies due to thrombosis, and this increases as the age group increases. The major outcomes are considered to be a recurrence, bleeding due to commercially available anti-coagulants, and deaths. The side effects associated with available anti-thrombotic drugs are a point of concern. Therefore, it is necessary to discover and develop an improvised benefit-risk profile drug, therefore, in search of alternative therapy for the treatment of thrombosis, marine sources have been used as promising treatment agents. They have shown the presence of sulfated fucans/galactans, fibrinolytic proteases, diterpenes, glycosaminoglycan, glycoside, peptides, amino acids, sterols, polysaccharides, polyphenols, vitamins, and minerals. Out of these marine sources, many chemicals were found to have anti-thrombotic activities. This review focuses on the recent discovery of anti-thrombotic agents obtained from marine algae, sponges, mussels, and sea cucumber, along with their mechanism of action and patents on its extraction process, preparation methods, and their applications. Further, the article concludes with the author's insight related to marine drugs, which have a promising future.
Keywords: cardiovascular